Developing Islamic Psychospiritual Guidelines for Covid-19 Task Counsellors - Rahman S.M.H.S.A.,; Mohd Azhar, Muhammad Hazim; Ramli, Mohd Anuar; Ahmad Sabki, Zuraida; Nasiruddin, Nabil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The Covid-19 pandemic has left significant implications on the emotional and psychological health as well as their personal well-being. As an effort in managing the problem, many individuals undergo counselling sessions with counsellors in the hope of gaining emotional and psychological support. However, the continuous dumping of client narratives during the Covid-19 pandemic has led to repercussions on emotional stress such as Secondary Traumatic Stress (STS) problems for these counsellors. By considering the solution to this problem from the Islamic perspective that states that human beings are also made up of the spiritual aspect, this study is aimed at developing an Islamic psychospiritual guideline for counsellors on duty during the Covid-19 pandemic. The study is conducted in three phases; the Needs Analysis Phase, Guideline Development Phase and Evaluation Phase. In the Needs Analysis Phase, literature review and interviews are employed to identify the items needed in the development of the guidelines. The guideline development phase is the process of completing the draft guidelines using the psychospiritual counselling theory as the foundation. This theory is an approach that combines the spiritual and religious aspects derived from the Qur’an and Hadith. Next is the evaluation phase where the guidelines developed are evaluated and validated by experts in the field of Islamic counselling, psychology and psychospiritual. This study presents the Islamic psychospiritual guidelines as preparation for counsellors in facing clients in an effort to avoid psychological disorders. The guidelines consist of two classifications namely; 1) mental and emotional preparation as a daily practice, before, during and after a session; and 2) spiritual preparation as a daily practice, before, during and after a session. It is hoped that these guidelines can be applied in the practice among Muslim counsellors as a holistic preparation that embraces the psychological and spiritual balance based on Islamic teachings.